Photography reinvented the collection of Robert E. Meyerhoff and Rheda Becker - Greenough, Sarah 1951-; Brookman, Philip 19XX-; Nelson, Andrea 19XX-; Ureña, Leslie J.; Waggoner, Diane ca. 21. Jh (Princeton University Press, 2016)
Exhibition held at the National Gallery (U.S.), Washington, D.C., September 30, 2016-March 5, 2017, of a private collection of thirty-five works gathered by Meyerhoff and Becker produced by nineteen artists
Exhibition dates: September 30, 2016 - March 5, 2017
Keywords: Meyerhoff, Robert / Photograph collections / Exhibitions; Becker, Rheda / Photograph collections / Exhibitions; National Gallery of Art -- Washington, DC; Photography, Artistic / Exhibitions; Fotografie; Ausstellungskatalog; Ausstellungskatalog -- National Gallery of Art -- 30.09.2016-05.03.2017 -- Washington, DC; Bildband; Katalog